The influence of modernisation of the radiotherapy base on the financial condition of a health care unit based on the example of Great Poland Cancer Centre - Śmigielska, Mirella (Contemporary Oncology/Współczesna Onkologia, 2008)
Aim of the study: Identification of causes and circumstances having an influence on the occurrence of the balance sheet loss of the Great Poland Cancer Centre, clarification of the influence of the centre’s expansion and investments connected with the modernisation of radiotherapy on the financial condition of the hospital. Material and methods: The article is based on 1) economic analysis concerning the years 1999-2007; data necessary to carry it out were obtained on the basis of financial reports – balance sheet, profit and loss statement and unit activity reports, taking into consideration medical statistics, 2) systems theory and change management. Results: Modernisation of the radiotherapy base in the Great Poland Cancer Centre caused an increase of depreciation costs and operating costs. Conclusions: Due to the fact that radiotherapy is an economically effective activity there are valid arguments supporting the temporary nature of the period of decrease in the hospital’s balance sheet results.